PENINGKATAN KECEPATAN MEMBACA PEMAHAMAN MELALUI MODEL PEMBELAJARAN BERBASIS KOMPUTER PADA SISWA KELAS V SD 1 JEKULO KABUPATEN KUDUS - Enny Dwi Lestariningsih; - Suhartono; Catur Karya Agus Priono S (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2015)
According to the initial test result in Year V, SD Negeri 1 Jekulo, Kudus Regency, it is known that the ability of speed reading and comprehension in Year V of the school was low. There were stillseveral students that had a low abilities of reading. There were only 31 students (68.89%) out of 45 students that achieved scores the same or higher than 70. Meanwhile, the number of students who got scores under 70 was 14 (31.11%). It is estimated that the students l ow abilities were due to thelack of variations of learning models of reading so that the motivations of the students to learn were low. A solution is needed to cope with such a condition in order to enhance the ability of reading comprehensions. The sol ution of f ered in this research is co mputer-based learning model as an effortof enhancing the ability of reading comprehensions in the Year V, SD Negeri 1 Jekulo. The problem in this research is that Can the ability of reading comprehensions be improved af terattending reading comprehensions learning through computer-based learning model using learning CDs? based on the research, the purpose of the research is to improve the students reading comprehension skills through computer-based learning model using learning CDs. The type of this research is classroom action research) using a qualitative method in form of recycle consisting of learning cycles. There are two cycles used in this research, such as classical learning management andindividual learning. The result of this research is that the computer-based learning method using learning CDs is able to improve the ability of reading speed and comprehension of the students of Year V, SD Negeri 1 Jekulo, Kudus Regency.Keywords: reading speed, learning model, computer